2020
DOI: 10.1111/trf.15664
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of HLA virtual cross‐matched platelet transfusions for platelet transfusion refractoriness in hematopoietic stem cell transplantation

Abstract: BACKGROUND Cross‐matched platelet (cross‐matched PLT) transfusion is effective for immune‐mediated platelet transfusion refractoriness (PTR), but is more costly and time‐consuming for physical cross‐match than using standard PLT units. Recent studies have reported the utility of human leucocyte antigens (HLA) virtual cross‐matched PLT (HLA‐matched PLT) that is defined as HLA‐A/B matched or no antibody against donor‐specific antigen. Here, we evaluated the effect of HLA‐matched PLTs for PTR in post hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Platelet crossmatching and HLA matching are frequently used, and the success rate of these strategies is comparable. [32][33][34]…”
Section: Identifying Compatible Platelet Unitsmentioning
confidence: 99%
“…Platelet crossmatching and HLA matching are frequently used, and the success rate of these strategies is comparable. [32][33][34]…”
Section: Identifying Compatible Platelet Unitsmentioning
confidence: 99%
“…This index was reported in six publications (8)(9)(10)(11)13,14), and the heterogeneity test showed no statistically significant difference (I 2 =43%, P=0.12) using the fixed-effect mode, and the obtained effective rate of the two intervention methods was compared (OR =4.90, 95% CI: 3.50-6.86, Z=9.23, P<0.00001), as shown in Figure 3.…”
Section: Comparison Of the Effective Rate Of Plt After Gene Matching And Unmatched Transfusionmentioning
confidence: 90%
“…Only publications (11) mentioned the use of randomization, without necessarily detailing the specific method. None of the publications mentioned whether there was classification concealment or a blind method implementation, and the phenomenon of case loss was reported in only three publications (8,9,11), although the data was still complete because the case loss was not included in the outcome statistics. There were no selective reporting in all included studies results, and other risk of bias was unknown, as shown in Table 2.…”
Section: Literature Bias Assessmentmentioning
confidence: 99%
“…Immune‐mediated platelet transfusion‐refractoriness is caused predominantly by patient antibodies against foreign class I human leukocyte antigens groups A and B (HLA‐A and HLA‐B) and, more rarely, by patient antibodies against foreign human platelet antigens (HPAs) 3–6 . While only the cause of 20%–25% of cases, immune‐mediated platelet transfusion‐refractoriness can be successfully mitigated by selecting platelet units that avoid recipient anti‐platelet antibodies 3,4,7–11 . Multiple in vitro approaches exist for the identification of compatible platelet inventory for such patients, including solid‐phase platelet crossmatches, class I HLA antibody (HLA‐Ab)/antigen testing, and HPA antibody/antigen testing 8–18 .…”
Section: Introductionmentioning
confidence: 99%
“…While only the cause of 20%–25% of cases, immune‐mediated platelet transfusion‐refractoriness can be successfully mitigated by selecting platelet units that avoid recipient anti‐platelet antibodies 3,4,7–11 . Multiple in vitro approaches exist for the identification of compatible platelet inventory for such patients, including solid‐phase platelet crossmatches, class I HLA antibody (HLA‐Ab)/antigen testing, and HPA antibody/antigen testing 8–18 . Each approach has diagnostic limitations, however, so algorithms integrating multiple approaches have been proposed 17,19 …”
Section: Introductionmentioning
confidence: 99%